2007
DOI: 10.1016/j.rmed.2006.04.010
|View full text |Cite
|
Sign up to set email alerts
|

In utero and childhood exposure to parental tobacco smoke, and allergies in schoolchildren

Abstract: Among early-life environmental factors, parental smoking (ETS) has been associated with adverse respiratory outcomes in children. The aim of the study was to evaluate whether parental smoking might lead to asthma and allergies taking into account family history of asthma, personal atopy, breast feeding as confounders and owing pets and day-care during the first 6 months of life as modifiers. About 9000 children of fourth and fifth grade were selected in six cities of France. About 7798 answered an epidemiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
3
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 23 publications
6
46
3
8
Order By: Relevance
“…Smoking during pregnancy affects fetal lung development especially when there is a family history of asthma and hypertension during pregnancy (1866,1867) and causes abnormal airway function (1868). Effects of ETS due to parental smoking on wheezing in early childhood have been described in epidemiologic studies (1869)(1870)(1871)(1872)(1873) but few have made an effort to discriminate between the effects of prenatal and postnatal exposure. Recent studies suggest that smoke exposure in utero may be at least as detrimental to respiratory health in early life as postnatal exposure to ETS (1874).…”
Section: Occupational Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking during pregnancy affects fetal lung development especially when there is a family history of asthma and hypertension during pregnancy (1866,1867) and causes abnormal airway function (1868). Effects of ETS due to parental smoking on wheezing in early childhood have been described in epidemiologic studies (1869)(1870)(1871)(1872)(1873) but few have made an effort to discriminate between the effects of prenatal and postnatal exposure. Recent studies suggest that smoke exposure in utero may be at least as detrimental to respiratory health in early life as postnatal exposure to ETS (1874).…”
Section: Occupational Agentsmentioning
confidence: 99%
“…Another study suggested that in utero exposure is more important (1875). There is not usually any association between atopy, rhinitis, eczema and parental smoking (1873). Counseling parents to stop smoking still remains an important policy.…”
Section: Occupational Agentsmentioning
confidence: 99%
“…Studies of environmental tobacco smoke (ETS) have found that it to be a risk factor for children's respiratory health in many developed countries or regions, for example in Italy [2], France [3], Portugal [4], Greece [5], Bulgaria [6], Singapore [7], Japan [8], USA [9][10][11] and Taiwan, China [12]. A study In Shanghai also found similar adverse effects from ETS [13].…”
mentioning
confidence: 99%
“…These risk factors may already act in utero and in early life [39]. Any study in the prevention and control of NCDs should consider these risk factors.…”
Section: Tobacco and Biomass Fuel Combustionmentioning
confidence: 99%